2020
DOI: 10.18203/2320-6012.ijrms20203454
|View full text |Cite
|
Sign up to set email alerts
|

High sensitive C reactive protein as an inflammatory indicator in preeclampsia

Abstract: Background: Preeclampsia is one of the most serious complications of pregnancy and one of the leading cause of maternal, prenatal morbidity and mortality. The present study was carried out to estimate serum high sensitive C- reactive protein in both mild and severe preeclampsia as an indicator of inflammation and to correlate Hs-CRP with blood pressure.Methods: A case control study was conducted in the Department of Biochemistry and Department of Obstetrics and Gynecology, MIMER Medical College and Bhausaheb S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 0 publications
9
7
0
Order By: Relevance
“…Preeclampsia was found in higher percentage among primigravida compared to multigravida, whereas this association was not significant. These findings are similar to studies conducted by Sayyed AAK et al, and Prerna B et al [9,10] . The average levels of weight, average levels of systolic and diastolic blood pressure levels were significantly higher among preeclamptic group compared to the normal pregnancy group.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Preeclampsia was found in higher percentage among primigravida compared to multigravida, whereas this association was not significant. These findings are similar to studies conducted by Sayyed AAK et al, and Prerna B et al [9,10] . The average levels of weight, average levels of systolic and diastolic blood pressure levels were significantly higher among preeclamptic group compared to the normal pregnancy group.…”
Section: Discussionsupporting
confidence: 92%
“…The similarity between the lesions of pre-eclampsia and atherosclerosis, together with the antifibrinolytic properties of Lp(a) has led to speculations of a common pathophysiological pathway [4] . The findings of Lp (a) in the present study is comparable with the studies conducted elsewhere [10,12] . In the present study, the average hsCRP levels were significantly among preeclamptic group (7.54±2.44 mg/dl) compared to normal pregnancy group (5.8±3.0mg/dl).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the study preeclampsia was more common among the primigravida (65% of mild preeclampsia and 73% of severe preeclampsia group were primigravida). Similar results are found in the study conducted by Guhan VN et al Indumati V. et al 11,14 Alterations in serum electrolytes levels indicate the underlying physiological and pathological changes of pregnancy. In our study, hypernatremia and hypokalemia were found in both mild and severe preeclampsia with highest derangement seen in the severe preeclamptic group (highest sodium levels: 147±3.4 mmol/l and lowest potassium levels: 3.5±0.4mmol/l).…”
Section: Discussionsupporting
confidence: 88%
“…Some studies of preeclampsia have shown abnormality in the transport of sodium and potassium pump across the vascular smooth muscle cell membrane, which is normally responsible for maintenance of blood pressure. 11,14 In the present study, hypomagnesemia was found among both the mild and severe preeclamptic patients (mild PE: 1.5±0.5 mg/dl. ; severe PE: 1.4±0.3mg/dL).…”
Section: Discussionsupporting
confidence: 53%